Measuring the Effectiveness of Fashion Blogger Endorsement on Students Buying Decision - Saraswati, Kania; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
The primary purpose of this paper is to measure the effectiveness of fashion blogger endorsement among students in Indonesia. It is expected through this study a more effective endorsement advertisement could be reached. the design methodology came from descriptive research which use questionnaire as the tool of data collection. A descriptive analysis, data categorization, and comparison of data between group of samples is used to analyze the data. The result of this research shows that fashion blogger considered as effective, as the results shows that more than 60% of respondents purchase the product that endorsed by the fashion blogger. A purchase is one of level which advertisement considered as effective. The research is conducted in three months due to the limited time. The researcher suggests to do the research in a longer time to measure more respondents and more variable that could measure fashion blogger advertisement effectiveness. This research could provide marketers a better understanding about fashion blogger endorsement among students so they can implement a more effective marketing through fashion blogger endorsement. This research is also useful for fashion blogger who wants to broaden their career as fashion blogger as they can see the consumerâ€™s perception about fashion blogger. fashion blogger endorsement as the object of research is new as there are not much research that measured the effectiveness of endorsement through fashion blogger. Â Keywords: fashion blogger, endorsement, advertising, advertising effectiveness, buying decision, consumer behavior----------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.